Trade Liberalization, Child Labor, and Schooling: Evidence from India - Eric Edmonds Nina Pavcnik Petia Topalova
Can the short and medium term adjustment costs associated with trade liberalization have long term consequences through their impact on child labor and schooling? Tariff changes can influence child labor and schooling through their effect on family incomes via the return to capital or the adult labor market, the return to schooling, the return to work for children, and consumption prices. We consider the impact of India's 1991 trade tariff reforms on child labor and schooling in India. Overall, in the 1990s, India experienced a dramatic decline in child labor and increase in schooling. However, communities that were heavily protected before liberalization do not experience as large a decline in child labor or increase in schooling. The data suggest that this failure to follow the national trend of diminishing work and increasing schooling stems principally from difficulty in affording school costs. Hence, short term trade adjustment assistance targeted at children in affected communities may easily ameliorate these potentially long term consequences of the trade adjustment process.